2019
DOI: 10.1037/tep0000231
|View full text |Cite
|
Sign up to set email alerts
|

Who’s on first? Supervising psychology trainees with disabilities and establishing accommodations.

Abstract: This research was developed to understand supervisors' experiences, attitudes, and biases when working with psychology trainees with disabilities, in order to better educate and support supervisors. An anonymous online survey that included 36 questions was developed based on previous literature on supervision and disability. Questions examined supervisors' knowledge of their responsibility in providing disability accommodations, their own experiences, and one of two randomly assigned vignettes to simulate a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 23 publications
2
56
0
Order By: Relevance
“…Additionally, faculty and supervisors may be unfamiliar with what resources and supports are available to or potentially helpful to trainees with disabilities, whereas disability service professionals may be unfamiliar with the nature and essential functions of professional psychology trainees. Supervisors may be unaware of procedures or resources for accommodating trainees with disabilities and thus may not offer them as options even when they are necessary and appropriate (Wilbur, Kuemmel, & Lackner, 2019). This may be particular salient when trainees have invisible disabilities (Wilbur et al, 2019), as supervisors may not even think to ask about accommodations or even feel that they can ask a trainee who does not appear to be disabled about potential accommodations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, faculty and supervisors may be unfamiliar with what resources and supports are available to or potentially helpful to trainees with disabilities, whereas disability service professionals may be unfamiliar with the nature and essential functions of professional psychology trainees. Supervisors may be unaware of procedures or resources for accommodating trainees with disabilities and thus may not offer them as options even when they are necessary and appropriate (Wilbur, Kuemmel, & Lackner, 2019). This may be particular salient when trainees have invisible disabilities (Wilbur et al, 2019), as supervisors may not even think to ask about accommodations or even feel that they can ask a trainee who does not appear to be disabled about potential accommodations.…”
Section: Discussionmentioning
confidence: 99%
“…Supervisors may be unaware of procedures or resources for accommodating trainees with disabilities and thus may not offer them as options even when they are necessary and appropriate (Wilbur, Kuemmel, & Lackner, 2019). This may be particular salient when trainees have invisible disabilities (Wilbur et al, 2019), as supervisors may not even think to ask about accommodations or even feel that they can ask a trainee who does not appear to be disabled about potential accommodations. Thus, even trainees who proactively seek out resources may have difficulty successfully utilizing them.…”
Section: Discussionmentioning
confidence: 99%
“…One participant in a previous study reported that they received no interview invitations for internship sites when they disclosed their disability on their application but received numerous interview invitations and successfully matched during the following cycle when they did not disclose their disability (Lund, Andrews, & Holt, 2016). Faculty and supervisors at internship sites often do not feel comfortable or competent working with trainees with disabilities (Wilbur et al, 2019); rather than addressing this gap in competency, supervisors may simply reject applicants who identify as or are perceived as having a disability. They may assume that a disabled applicant cannot complete the essential functions required of interns at the site and simply reject them without ever asking if the applicant can perform those functions with or without reasonable accommodations.…”
Section: Discussionmentioning
confidence: 99%
“…Although professional psychology trainees with all types of disabilities encounter ableist barriers and discrimination, the nature of that ableism may differ by disability type. For example, trainees with invisible disabilities may face skepticism or doubt when disclosing their disability (Wilbur et al, 2019) whereas trainees with visible disability may face automatic assumptions of incompetence based on others' assumptions about their disability (Lund, Andrews, & Holt, 2016). Additionally, trainees with certain types of disabilities may face specific barriers related to accessing communication, their physical environment, or course materials (Andrews et al, 2013;Hauser et al, 2000;Joshi, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of supporting multiply marginalized trainees with disabilities, we recommend that all programs create an antioppressive and antiableist culture (Lund, Wilbur, et al, 2020; Wilbur et al, 2019). In other words, faculty and administrators must be willing to acknowledge explicit and implicit ableism and other forms oppression within their program policies, practices, and culture.…”
Section: Strategies For Recruiting and Retaining Multiply Marginalize...mentioning
confidence: 99%